Liquidity constraints in the U.S. housing market - Denis Gorea; Virgiliu Midrigan (Danmarks Nationalbank, 2019)
We study the severity of liquidity constraints in the U.S. housing market using a life-cycle model with uninsurable idiosyncratic risks in which houses are illiquid, but agents have the option to extract home equity by refinancing their long-term mortgages. The model implies that three quarters of homeowners are liquidity constrained and willing to pay an average of 5 cents to extract an additional dollar of liquidity from their home. Most homeowners value liquidity for precautionary reasons, anticipating the possibility of income declines and the need to make mortgage payments in future periods. Mortgage assistance policies structured as credit lines to homeowners who experience a shortfall in income greatly reduce the severity of liquidity constraints.
Keywords: E21; E30; 330; Home equity extraction; liquidity constraints; mortgage refinancing